Larvae of Eight Eastern North American Sweltsa (Plecoptera: Chloroperlidae) - Stark, Bill P. (Illiesia, 2011)
Larval descriptions are provided for eight eastern Nearctic species of Sweltsa. Larvae of Sweltsa hoffmani Kondratieff & Kirchner, S. lateralis (Banks), S. mediana (Banks), S. naica (Provancher), S. palearata Surdick, S. pocahontas Kirchner & Kondratieff and S. urticae (Ricker) are described for the first time and compared with S. onkos (Ricker). A provisional key is presented for larvae of these eastern Nearctic species.
Keywords: entomology; stoneflies; Sweltsa; Plecoptera; United States of America; USA; larval descriptions; Eastern North America; entomologija; larve; vrbnice